2022
DOI: 10.1111/ppe.12890
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary and neuroimaging findings in preterm born very low birthweight individuals from birth to 28 years of age: A systematic review of a Norwegian prospective cohort study

Abstract: Background Children born preterm with very low birthweight (VLBW) face long‐lasting neurodevelopmental challenges, where multidisciplinary assessments are warranted. The International Classification of Functioning, Disability and Health (ICF) provides a framework for understanding and conceptualising these outcomes. Objectives We aimed to review clinical and neuroimaging findings from birth to adulthood in a Norwegian cohort of individuals born preterm with VLBW (gestational age <37 weeks, birthweight ≤1500 g)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 89 publications
0
27
0
Order By: Relevance
“…The one-stage IPD analysis could be implemented either using a fixed-effects or random-effects model. [61] In our study, cohort study participants were enrolled across different geographical regions, ages and time frames, which suggests the presence of systematic differences across Additional details for each study can be found in published research as follows: BLS [46], VICS [47], NTNU LBW Life [50], EPICure [48] and NZ-VLBW [ 1). Study participants also shared common characteristics that were fixed across geographic and socioeconomic dimensions caused by study-specific or countryspecific factors.…”
Section: Empirical Analysesmentioning
confidence: 99%
“…The one-stage IPD analysis could be implemented either using a fixed-effects or random-effects model. [61] In our study, cohort study participants were enrolled across different geographical regions, ages and time frames, which suggests the presence of systematic differences across Additional details for each study can be found in published research as follows: BLS [46], VICS [47], NTNU LBW Life [50], EPICure [48] and NZ-VLBW [ 1). Study participants also shared common characteristics that were fixed across geographic and socioeconomic dimensions caused by study-specific or countryspecific factors.…”
Section: Empirical Analysesmentioning
confidence: 99%
“…For example, in adolescence and adulthood, very preterm survivors continue to perform below term peers across a range of cognitive domains [2][3][4] which is likely related to altered cerebral maturation and white matter microstructure. 3 Regarding health status, older survivors tend to be less active, have poorer motor skills and cardiorespiratory fitness, lower bone density and higher systolic blood pressure and insulin resistance. 3,5 These findings are concerning and highlight the need to study the health of very preterm survivors into middle age and beyond.…”
mentioning
confidence: 99%
“…Papers in this special issue demonstrate that the developmental and health issues observed in early childhood are likely to reflect persistent life‐long concerns. For example, in adolescence and adulthood, very preterm survivors continue to perform below term peers across a range of cognitive domains 2–4 which is likely related to altered cerebral maturation and white matter microstructure 3 . Regarding health status, older survivors tend to be less active, have poorer motor skills and cardiorespiratory fitness, lower bone density and higher systolic blood pressure and insulin resistance 3,5 .…”
mentioning
confidence: 99%
See 2 more Smart Citations